Microchip capillary electrophoresis: improvements using detection geometry, on-line preconcentration and surface modification - Guan, Qian, author; Henry, Charles S., advisor; Strauss, Steven H., committee member; Van Orden, Alan K., committee member; Krummel, Amber, committee member; Hanneman, William H., committee member (Colorado State University. Libraries, 2012)
Capillary electrophoresis and related microfluidic technologies have been utilized with great success for a variety of bioanalytical applications. Microchip capillary electrophoresis (MCE) has the advantages of decreased analysis time, integrated sample processing, high portability, high throughput, minimal reagent consumption, and low analysis cost. This thesis will focus on the optimization of our previous microchip capillary electrophoresis coupled electrochemical detection (MCE-ECD) design for improved separation and detection performance using detection geometry, on-line preconcentration and surface modification. The first effort to improve detection sensitivity and limits of detection (LODs) of our previous MCE-ECD system is established by an implementation of a capillary expansion (bubble cell) at the detection zone. Bubble cell widths were varied from 1× to 10× the separation channel width (50 μm) to investigate the effects of electrode surface area on detection sensitivity, LOD, and separation efficiency. Improved detection sensitivity and decreased LODs were obtained with increased bubble cell width, and LODs of dopamine and catechol detected in a 5× bubble cell were 25 nM and 50 nM respectively. In addition, fluorescent imaging results demonstrate ~8% to ~12% loss in separation efficiency in 4× and 5× bubble cell, respectively. Another effort for enhancing detection sensitivity and reducing LODs involves using field amplified sample injection and field amplified sample stacking. Stacking effects were shown for both methods using DC amperometric and pulsed amperometric detections. Decreased LODs of dopamine were achieved using both on-line sample preconcentration methods. The use of mixed surfactants to affect electroosmotic flow (EOF) and alter separation selectivity for electrophoretic separations in poly(dimethylsiloxane) (PDMS) is also presented in this thesis. First the effect of surfactant concentration on EOF was studied using the current monitoring method for a single anionic surfactant (sodium dodecyl sulfate, SDS), a single zwitterionic surfactant (N-tetradecylammonium-N,N-dimethyl-3-ammonio-1-propane sulfonate, TDAPS), and a mixed ionic/zwitterionic surfactant system (SDS/TDAPS). SDS increases the EOF as reported previously while TDAPS shows an initial increase in EOF followed by a reduction in EOF at higher concentrations. The addition of TDAPS to a solution containing SDS makes the EOF decrease in a concentration dependent manner. The mixed SDS/TDAPS surfactant system allows tuning of the EOF across a range of pH and concentration conditions. After establishing EOF behavior, the adsorption/desorption rates were measured and show a slower adsorption/desorption rate for TDAPS than SDS. Next, capacitively coupled contactless conductivity detection (C4D) is introduced for EOF measurements on PDMS microchips as an alternative to the current monitoring method to improve measurement reproducibility. EOF measurements as a function of the surfactant concentration were performed simultaneously using both methods for three nonionic surfactants, (polyoxyethylene (20) sorbitan monolaurate (Tween 20), polyoxyethylene octyl phenyl ether (Triton X-100), polyethylene glycol, (PEG 400)), mixed ionic/nonionic surfactant systems (SDS/Tween 20, SDS/Triton X-100, and SDS/PEG 400) and mixed zwitterionic/nonionic surfactant systems (TDAPS/Tween 20, TDAPS/Triton X-100, and TDAPS/PEG 400). EOF for the nonionic surfactants decreases with increasing surfactant concentration. The addition of SDS or TDAPS to a nonionic surfactant increases EOF relative to the pure nonionic surfactant. Next, separation and electrochemical detection of two groups of model analytes were explored using mixed surfactant systems. Similar analyte resolution with greater peak heights was achieved with mixed surfactant systems relative to the single surfactant system. Finally, the utility of mixed surfactant systems to achieve improved separation chemistry of biologically relevant compounds in complex sample matrixes was demonstrated in two applications, which include the detection of catecholamine release from rat pheochromocytoma (PC12) cells by stimulation with 80 mM K+ and the detection of reduced glutathione (GSH) in red blood cells (RBCs) exposed to fly ash suspension as a model environmental oxidant.
Keywords: surface modification with mixed surfactants; microchip capillary electrophoresis; on-line sample preconcentration using field amplified stacking techniques; detection geometry modification with bubble cell; electrochemical detection